Distribution of herbivorous fish is frozen by low temperature - Vejříková, Ivana (Jihočeská univerzita, 2019)
The number of herbivores in populations of ectothermic vertebrates decreases with increasing latitude. At higher latitudes, fish consuming plant matter are exclusively omnivorous. We assess whether omnivorous fish readily shift to herbivory or whether animal prey is typically preferred. We address temperature as the key factor causing their absence at higher latitudes and discuss the potential poleward dispersion caused by climate changes. A controlled experiment illustrates that rudd (Scardinius erythrophthalmus) readily utilize plant matter at water temperatures above 20 °C and avoid its consumption below 20 °C. Field data support these results, showing that plant matter dominates rudd diets during the summer and is absent during the spring. Utilizing cellulose requires the enzyme cellulase, which is produced by microorganisms growing at temperatures of 15-42 °C. Water temperatures at higher latitudes do not reach 15 °C year-round; at our latitude of 50°N 150 days/year. Hence, the species richness of omnivorous fish decreases dramatically above 55° latitude. Our results provide support for the hypothesis that strict herbivorous specialists have developed only in the tropics. Temperatures below 15 °C, even for a short time period, inactivate cellulase and cause diet limitations for omnivorous fish. However, we may expect increases in herbivory at higher latitudes caused by climate change.
Distribution of herbivorous fish is frozen by low temperature
Keywords: cellulase; climate change; latitudinal gradient; macrophytes; Scardinius erythrophthalmus; temperature pattern; cellulase; climate change; latitudinal gradient; macrophytes; Scardinius erythrophthalmus; temperature pattern